HEALTHY LIFESTYLE - Mamatqobilova Sadoqat; Ramazanova N.T (Scholar Express Journals, 2021)
This study covers in detail the benefits of a healthy lifestyle,proper nutrition,exercise,and diet in the human body,healthy living involves more than physical health,it also includes mental and emotional health.
Keywords: Healthy; diet; energy; sports